2004
DOI: 10.1097/01.asn.0000131272.06958.de
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Mediated Renal Injury Is Dependent on Signaling via the JNK Pathway

Abstract: Abstract. Macrophage accumulation is a prominent feature in most forms of human glomerulonephritis and correlates with renal dysfunction. Macrophages can directly mediate acute renal injury in animal models, but the mechanisms of macrophage activation required for mediating renal injury are unknown. This study examined whether activation of the Jun amino terminal kinase (JNK) signaling pathway is necessary for macrophage-mediated renal injury. An adoptive transfer model was used in which rats were immunized wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 38 publications
3
35
0
Order By: Relevance
“…40 Another report showed that proteinuria and glomerular cell proliferation induced by anti-GBM was dependent on JNK activity in bone marrow macrophages. 44 Taken together, the present study and the previous reports support the hypothesis that loss of ABIN1 K63 and linear polyubiquitin binding leading to increased NF-kB and MAPK activity participates in the development of SLE and LN. Variants in the ABIN1 gene TNIP1 have been reported in patients with SLE, suggesting a role for ABIN1 in human autoimmune disease.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…40 Another report showed that proteinuria and glomerular cell proliferation induced by anti-GBM was dependent on JNK activity in bone marrow macrophages. 44 Taken together, the present study and the previous reports support the hypothesis that loss of ABIN1 K63 and linear polyubiquitin binding leading to increased NF-kB and MAPK activity participates in the development of SLE and LN. Variants in the ABIN1 gene TNIP1 have been reported in patients with SLE, suggesting a role for ABIN1 in human autoimmune disease.…”
supporting
confidence: 75%
“…26 A role for enhanced MAPK signaling in the development of GN has been suggested in several reports. [40][41][42][43][44] Stambe et al showed enhanced active p-p38 MAPK in glomeruli, tubules, and myofibroblast and infiltrated neutrophils and macrophage in kidney biopsy specimens from patients with different types of proliferative GN, including class III/IV LN, and found that elevated p-p38 MAPK correlated with renal dysfunction and histopathology. 41 The same group showed in a separate study that administration of a specific p38 MAPK inhibitor prevented renal injury and renal function loss from anti-glomerular basement membrane (GBM)-induced GN in rats.…”
mentioning
confidence: 99%
“…Macrophages also have been postulated as mediators of tubular epithelial cell apoptosis (51). CC-401 treatment had no effect on interstitial macrophage accumulation in the obstructed kidney; however, we cannot rule out that JNK signaling may have a role in macrophage activation that leads to tubular epithelial cell apoptosis in the UUO model, because previous adoptive transfer studies in rat anti-glomerular basement membrane disease have shown that blockade of JNK signaling in macrophages can reduce substantially macrophage-mediated renal injury without any effect on macrophage recruitment into the injured kidney (52).…”
Section: Discussionmentioning
confidence: 89%
“…The role of JNK in macrophage-mediated renal injury in this model was addressed using an adoptive transfer approach. Administration of a JNK inhibitor to cultured macrophages before their transfer into leukocyte-depleted rats given anti-GBM serum did not prevent macrophage recruitment into glomeruli, but it profoundly inhibited the induction of proteinuria and mesangial cell proliferation indicating that the macrophage response had been modified (35). Indeed, JNK blockade markedly blunted the TNF-α response in cultured macrophages (35).…”
Section: Jnk In Glomerular Diseasementioning
confidence: 99%